High SIRT1 expression is a negative prognosticator in pancreatic ductal adenocarcinoma - Stenzinger, Albrecht; Endris, Volker; Klauschen, Frederick; Sinn, Bruno; Lorenz, Katja; Warth, Arne; Goeppert, Benjamin; Ehemann, Volker; Muckenhuber, Alexander; Kamphues, Carsten; Bahra, Marcus; Neuhaus, Peter; et al. (BMC cancer, 2013)
Several lines of evidence indicate that Sirt1, a class III histone deacetylase (HDAC) is implicated in the initiation and progression of malignancies and thus gained attraction as druggable target. Since data on the role of Sirt1 in pancreatic ductal adenocarcinoma (PDAC) are sparse, we investigated the expression profile and prognostic significance of Sirt1 in vivo as well as cellular effects of Sirt1 inhibition in vitro.